2014
DOI: 10.1128/jvi.02983-13
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of True Late (γ2) Cytomegalovirus Genes Requires UL92 Function That Is Conserved among Beta- and Gammaherpesviruses

Abstract: Human cytomegalovirus-encoded UL92 plays an essential role in viral replication that has not been resolved. We show here that this gene controls the accumulation of true late (γ2) viral transcripts, a property shared with several other recently evaluated genes (UL79, UL87, UL91, and UL95) conserved among beta- and gammaherpesviruses. When the UL92 mutant virus was evaluated, function was fully complemented by either the natural protein or the homologous Rh127 protein from rhesus cytomegalovirus. N-terminal epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 67 publications
2
29
0
Order By: Relevance
“…In the case of MHV-68, five proteins (ORF18, ORF24, ORF30, ORF31, and ORF34) were found to be necessary for the expression of the MHV-68 late genes. Analogs for these proteins in CMV (UL79, UL87, UL91, UL92, and UL95, respectively) were also found to be necessary for late gene expression (26)(27)(28)(29)(30)(31)(32)(33). Interestingly, EBV also encodes five putative analogs (BVLF1.5, BcRF1, BDLF3.5, BDLF4, and BGLF3, respectively).…”
Section: Identification Of Viral Proteins Required For Late Gene Exprmentioning
confidence: 99%
“…In the case of MHV-68, five proteins (ORF18, ORF24, ORF30, ORF31, and ORF34) were found to be necessary for the expression of the MHV-68 late genes. Analogs for these proteins in CMV (UL79, UL87, UL91, UL92, and UL95, respectively) were also found to be necessary for late gene expression (26)(27)(28)(29)(30)(31)(32)(33). Interestingly, EBV also encodes five putative analogs (BVLF1.5, BcRF1, BDLF3.5, BDLF4, and BGLF3, respectively).…”
Section: Identification Of Viral Proteins Required For Late Gene Exprmentioning
confidence: 99%
“…These five viral ORFs play an important role in activating viral late gene promoters, and it has also been shown that ORF30 and -34 are critical for recruiting RNA polymerase II (Pol II). More recently, studies in cytomegalovirus (CMV), a betaherpesvirus, have demonstrated that the UL79, -87, -91, -92, and -95 genes, homologous to MHV-68 ORF18, -24, -30, -31, and -34, respectively, are also essential for viral late gene expression (18)(19)(20)(21)(22). The evidence strongly suggests that beta-and gammaherpesviruses share a similar mechanism to regulate late gene expression.…”
mentioning
confidence: 94%
“…EBV BAC DNAs were digested with BamHI or EcoRI and separated in an agarose gel. 5. Immunoprecipitation (IP) was carried out using anti-Flag antibody, and the results were detected by Western blotting using anti-Myc, anti-HA, and anti-Flag antibodies.…”
Section: Acknowledgmentsmentioning
confidence: 99%